EXPLORING BIM ADOPTION AMONG MALAYSIAN CONSTRUCTION ORGANISATIONS - Wan Nur Syazwani Wan Mohammad (Journal of Islamic, Social, Economics and Development, 2021)
Building Information Modelling (BIM) is a digital industry in construction and a solution for the construction industry in approaching the fourth industrial revolution (4.0). To date, Building Information Modelling (BIM) is used to improve visualization and productivity; to better the coordination of construction drawings and communication; create faster delivery; and lower costs. However, recent studies have revealed that construction organisations are reluctant to adopt BIM in their construction process. Hence, this research aims to seek and explore the overview of BIM adoption among Malaysian Construction organisations. In order to do so, a qualitative approach in the form of unstructured interviews were used in this study to explore BIM adoption among contractor organisations. Then, the findings were analysed using content analysis. Thus, the findings indicated that there was still lack of BIM adoption among construction organisations and the adoption among construction organisations is still at an infancy stage. As a result, this paper is able to provide insight into the Malaysian construction organisation development and form the basis of a valuable BIM strategy, especially for the local construction industry.